Use of Chinese Herbal Medicines Is Related to a Reduction in Depression Risk Among Patients With Insomnia: A Matched Cohort Study - Chiao, Yun-Wen; Livneh, Hanoch; Guo, How-Ran; Chen, Wei-Jen; Lu, Ming-Chi; Lin, Miao-Chiu; Yeh, Chia-Chou; Tsai, Tzung-Yi (Frontiers in Neurology, 2021)
Objective. Subjects with insomnia have a higher risk of depression, thus possibly making them live with serious health conditions. To date, information regarding the effect of Chinese herbal medicines (CHMs), a commonly used complementary and alternative medicine, on depression risk among people with insomnia is still unknown. This study aimed to investigate the effect of CHMs on risk of depression among individuals with insomnia. Methods. This cohort study used a national health insurance database to identify 68,573 subjects newly diagnosed with insomnia, aged 20-70 years, who received treatment between 1998 and 2010. Using propensity score matching, we randomly selected 26,743 CHM users and 26,743 non-CHM users from this sample. All enrollees were followed to the end of 2012 to identify any treatemnt for depression as the end point. Cox proportional hazards regression was used to compute the adjusted hazard ratio (aHR) of depression by CHM use. Results. After utilizing the propensity score matching, we randomly selected 26,743 CHMs users and 26,743 non-CHMs users from this sample. During follow up, 3,328 CHMs users and 6,988 non-CHMs users developed depression at incidence rates of 17.24 and 37.97 per 1,000 person-years, respectively. CHMs users had a lower depression risk than the non-CHMs users (adjusted hazard ratio = 0.44; 95% Confidence Interval, 0.42-0.46). The greatest effect was observed for those taking CHMs for more than two years. Gegen, Huangqin, Dan-Shen, Beimu, Dahuang, Shegan, Shu-jing-huo-xue-tang, Ge-gen-tang, Shao-yao-gan-cao-tang and Píng wèi sǎn were significantly associated with a lower risk of depression. Conclusions. Findings from this study demonstrated that adding CHMs to the routine clinical care significantly benefitted those with insomnia.